OPINI PUBLIK MENGENAI ISU “SRI MULYANI MAU ORANG KAYA BAYAR PAJAK LEBIH BANYAK” DALAM MEDIA INSTAGRAM @narasinewsroom - Mochamad Rafi; Nurhayani Saragih; Sri Wahyuning Astuti (Indonesian Journal of Digital Public Relations (IJDPR), 2023)
The issue that has been developing in recent times is the issue of the policy of the minister of finance who wants to issue a policy that the rich must pay higher than before, this policy is taken in a step to deal with Indonesia's economic recovery which was previously sluggish due to Covid-19 pandemic. The purpose of this study is to analyze Positive public opinion, negative public opinion, and neutral on the post 'Sri Mulyani Mau Orang Kaya Bayar Pajak Lebih Banyak' in Instagram Media @narasinewsroom Period July 2, 2021 In this study, researchers used the concept of public opinion which has been categorized into opinion positive, negative, and neutral.In this study, the study population took all comments on the post "Sri Mulyani Wants Rich People to Pay More Taxes" on @narasinewsroom Instagram account as many as 526 and the sample in this study was 228 comments. The data collection technique uses random sampling techniques. in testing validity and reliability using reliability between coders using hostly formulas. The results showed that there were 82 positive opinions (36% of comments), negative opinions categories got 86 frequency results (38% of comments) and neutral opinions that got frequency results of 60 (26% comments). Keywords: public relations, new media, public opinion